Sedative and clinical effects of the pharmacopuncture with xylazine in dogs - Cassu, Renata Navarro; Melchert, Alessandra [UNESP]; Bignelli Canoa, Jiancarlo Tortoza; Oliveira Martins, Paula Denise de (Acta Cirúrgica Brasileira, 2014)
PURPOSE: To investigate the sedative and clinical effects of the pharmacopuncture with xylazine, compared to the conventional dose of a intramuscular injection in dogs.METHODS: Twelve dogs were randomly distributed in two groups of six animals and treated as follows: control group (X-IM): 1mg kg(-1) of xylazine given intramuscularly (IM); pharmacopuncture group (X-Yintang): 0.1mg kg(-1) of xylazine diluted to 0.5 mL of saline injected into the Yin Tang acupoint. Heart rate, cardiac rhythm (ECG), systolic arterial blood pressure (SABP), respiratory rate (RR), rectal temperature (RT), blood glucose concentration, degree of sedation and adverse effects were evaluated.RESULTS: Sedative effect was observed in both groups. The degree of sedation was greater in X-IM only at 15 min when compared with X-Yintang group. Cardiovascular established was observed in X-Yintang group, while marked reduction in the HR and increased incidence of ECG abnormalities were detected in X-IM. In both treatment groups, minimal changes were observed in relation to SABP, RR, RT and blood glucose. High incidence (66%) of vomiting was observed in X-IM, while this adverse effect was absent in X-Yintang.CONCLUSION: Pharmacopuncture with xylazine induced clinically relevant sedative effects in dogs, with the advantage of reduction of undesirable side effects associated with alpha(2)-agonists, including bradycardia, cardiac arrhythmias, and emesis.
Keywords: Acupuncture; Sedation; Anxiolytic Agents; Xylazine; Dogs